Seletividade fisiológica de inseticidas utilizados em algodoeiro para Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) - Costa, Mariana Abreu (2017)
Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) is capable to parasitize eggs of several lepidopteran species present that can feed on cotton plants and for this reason must be conserved in this crop. The objective of this work was to evaluate the selectivity of the insecticides teflubenzuron, thiodicarb, chlorfenapyr, flupyradifurone and methomyl in their higher dosages recommended for pest control in the cotton crop to the parasitoid T. pretiosum in its immature and adult phases. Teflubenzuron and flupyradifurone caused a low reduction in emergence (F1) when applied on the egg-larva and pre-pupal stages, and therefore were classified as harmless. Teflubenzuron caused a low reduction in parasitism (F1) and did not affect the survival of females (F1), and was considered harmless. Chlorfenapyr and teflubenzuron caused a low reduction in the emergence (F2) and were classified as harmless to the parasitoid. Teflubenzuron reduced the parasitism of adults (F0) who fed on honey treated with this insecticide. Methomyl and thiodicarb were the most toxic insecticides for T. pretiosum in all exposure tests. In the contaminated surface contact test, flupyradifurone was considered slightly harmful; chlorfenapyr was moderately harmful, and thiodicarb and methomyl were harmful. In the residual persistence bioassay, chlorfenapyr, thiodicarb and methomyl were classified as persistent. Teflubenzuron caused a low toxicity to the immature and adult phases of T. pretiosum. For this reason, this insecticide should be preferred in integrated pest management programs that aim the conservation of this species in the cotton crops.